Information entropy and ranking of IBOVESPA companies: the relevance of environmental innovation - Ferreira, Lucas Benedito Gomes Rocha (2022)
This study analyzes the weights of multidimensional performance indicators to determine the ranking of the companies listed in  Bovespa index. This is a quantitative research using the multicriteria data entropy method, in which the indicators of the environmental, social, governance, economic-financial and market dimensions were obtained through the Refinitiv Eikon database. Thus, it was possible to establish the indicators weights for each year in order to determine  the rankings of the companies at sector and general level. The environmental innovation variable was responsible for the greater information relevance, while the indicators such as return on net worth and financial leverage obtained the lowest weights. As for the ranking, Renner occupied the first place, which makes it possible to infer that this company has been standing out in the indicators portrayed with higher weight. In addition, the communication and public utility sectors presented the highest mean scores, while the health and energy segments had the lowest mean performances. These results indicate the relevance of providing corporate information to reach investors, increasingly concerned with good management practices and socio-environmental indicators. Moreover, the findings suggest that innovating on environmental issues does not consist of a priority for the companies in the sample, raising the question whether these organizations visualize the legitimacy or returns of successful innovations as rewards of the investments made. Research contributes by pointing out that companies with best environmental practices can obtain more benefits, as well as the society, before the quality of life and environmental preservation.